KONSEP MANUSIA MENURUT ISLAM - Sitti Rahmatiah (240-540X)
Regarding the process of the creation of man many theories appear before the revelation of the Koran. From the start the theory of Aristotle, Louis Pasteur, to Charles Darwin. They are trying to uncover about where the origin of life and living. Since then (exactly 1860) emerged a new theory which states that all life comes from previous life. Although the new theory seems to be more intense and irrational, but it is still not able to describe the "mystery" of life itself. Because of these theories can not provide answers to questions about what is the origin of the first life. Because of that, people get confused. In medieval times-Karim al-Qur'anul and arguably one burglar door darkness of this theory with the facts of human creation is very complex and magical.